¡Olvidar el semitismo! - Massad, Joseph (El Colegio de México A.C., 2014)
This paper reflects on the memory of Freud in relation to the history of Semitism from the end of the 18th century, as a foundational moment in orientalism, anti-Semitism and the representation of Arabs, Muslims and Jews in the 19th century. It reprises the analysis of Edward Said, who connects it to the ongoing ecumenical liberal attempt to bring Judaism, Christianity and Islam together under the broad umbrella of “Abrahamic religions,” a concept evoked by Jacques Derrida towards the end of his life. Much of the liberal equivalence of these three religions is predicated on an insistence on forgetting their differences, one the histories of Semitism and anti-Semitism constantly recall.